The fire endurance of reinforced concrete structures - Vickers, Edward F (My University, 1974)
The material behaviour of concrete at elevated temperatures has been investigated. A series of tests was performed to verify and add to information available in the literature. This information has been used to model the behaviour of pinned end columns and the behaviour of columns in a building frame when subjected to fire exposure. A computer program was written to analyze rigid frames. This program employs an iterative procedure to approximate the inelastic behaviour of the frame.
Keywords: Engineering; Engineering